Temperature-dependent breakdown of hydrogen peroxide-treated ZnO and TiO(2) nanoparticle agglomerates - Sabuncu, Sinan (Beilstein J Nanotechnol, 2015)
Metal oxide nanoparticles (MONPs) are used in a variety of applications including drug formulations, paint, sensors and biomedical devices due to their unique physicochemical properties. One of the major problems with their widespread implementation is their uncontrolled agglomeration. One approach to reduce agglomeration is to alter their surface chemistry with a proper functionality in an environmentally friendly way. In this study, the influence of hydrogen peroxide (H(2)O(2)) treatment on the dispersion of ZnO and TiO(2) nanoparticle (NP) agglomerates as a function of temperature is studied. The H(2)O(2) treatment of the MONPs increases the density of hydroxyl (–OH) groups on the NP surface, as verified with FTIR spectroscopy. The influence of heating on the dispersion of H(2)O(2)-treated ZnO and TiO(2) NPs is investigated using dynamic light scattering. The untreated and H(2)O(2)-treated ZnO and TiO(2) NP suspensions were heated from 30 °C to 90 °C at 5 °C intervals to monitor the breakdown of large aggregates into smaller aggregates and individual nanoparticles. It was shown that the combined effect of hydroxylation and heating enhances the dispersion of ZnO and TiO(2) NPs in water.